2011
DOI: 10.1371/journal.pone.0021010
|View full text |Cite
|
Sign up to set email alerts
|

Lineage Relationship of Direct-Developing Melanocytes and Melanocyte Stem Cells in the Zebrafish

Abstract: Previous research in zebrafish has demonstrated that embryonic and larval regeneration melanocytes are derived from separate lineages. The embryonic melanocytes that establish the larval pigment pattern do not require regulative melanocyte stem cell (MSC) precursors, and are termed direct-developing melanocytes. In contrast, the larval regeneration melanocytes that restore the pigment pattern after ablation develop from MSC precursors. Here, we explore whether embryonic melanocytes and MSCs share bipotent prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Recovering melanoblasts emerge at the DRG and migrate along the spinal nerves Larval melanophores can regenerate if chemically or genetically ablated (Yang and Johnson, 2006;Hultman et al, 2009;Tryon et al, 2011). To investigate whether these newly formed melanophores originated from the putative DRG-associated stem cells, we depleted the directly differentiating melanophores with a mitfamorpholino.…”
Section: Stationary Mps Are Associated With Drgsmentioning
confidence: 99%
“…Recovering melanoblasts emerge at the DRG and migrate along the spinal nerves Larval melanophores can regenerate if chemically or genetically ablated (Yang and Johnson, 2006;Hultman et al, 2009;Tryon et al, 2011). To investigate whether these newly formed melanophores originated from the putative DRG-associated stem cells, we depleted the directly differentiating melanophores with a mitfamorpholino.…”
Section: Stationary Mps Are Associated With Drgsmentioning
confidence: 99%
“…This means that integration events can happen before fate segregation, generating both lineages (bipotential labelings), or after fate segregation, labeling only a single lineage. We had shown previously that ~60% of clones were bipotential, and the remainder generated only ontogenetic melanocytes or regeneration melanocytes (Tryon et al, 2011). Under Model 1 (Fig.…”
Section: Research Articlementioning
confidence: 84%
“…We have previously shown that all lineages that contain an MSC probably come from a neural crest precursor that will also produce an ontogenetic melanocyte lineage (Fig. 5A) (Tryon et al, 2011). Based on this model, we could imagine three possible ways to disrupt MSC establishment: (1) death of the neural crest precursor (Fig.…”
Section: The Role Of Kit Signaling In Msc Fate Determinationmentioning
confidence: 98%
See 2 more Smart Citations